To Explore Intracerebral Hematoma with a Hybrid Approach and Combination of Discriminative Factors - Chiu, Hui-Chu; Chiu, Deng-Yiv; Lee, Yao-Hsien; Wang, Chih-Cheng; Wang, Chen-Shu; Lee, Chi-Chung; Ying, Ming-Hsiung; Wu, Mei-Yu; Chang, Wen-Chih (Methods of Information in Medicine, 2016)
Objectives: To find discriminative combination of influential factors of Intracerebral hematoma (ICH) to cluster ICH patients with similar features to explore relationship among influential factors and 30-day mortality of ICH. Methods: The data of ICH patients are collected. We use a decision tree to find discriminative combination of the influential factors. We cluster ICH patients with similar features using Fuzzy C-means algorithm (FCM) to construct a support vector machine (SVM) for each cluster to build a multi-SVM classifier. Finally, we designate each testing data into its appropriate cluster and apply the corresponding SVM classifier of the cluster to explore the relationship among impact factors and 30-day mortality. Results: The two influential factors chosen to split the decision tree are Glasgow coma scale (GCS) score and Hematoma size. FCM algorithm finds three centroids, one for high danger group, one for middle danger group, and the other for low danger group. The proposed approach outperforms benchmark experiments without FCM algorithm to cluster training data. Conclusions: It is appropriate to construct a classifier for each cluster with similar features. The combination of factors with significant discrimination as input variables should outperform that with only single discriminative factor as input variable.
Keywords: Intracerebral hematoma; Glasgow coma scale score; Fuzzy C-means algorithm; support vector machine; decision tree